Critical Analysis of Cybercrimes in Pakistan: Legislative Measures and Reforms - Jibran Jamshed; Waheed Rafique; Khurram Baig; Waqas Ahmad (International Journal of Business and Economic Affairs, 2022)
Cybercrimes are increasing at a rapid pace in Pakistan. The current study explores the issue of cybercrimes in Pakistan. It aims to explore all the legislation dealing with cybercrimes in Pakistan. The study first described the cybercrimes and all those factors that are responsible for the cybercrimes. It explored all the common methods employed by criminals for cybercrimes. The study then critically evaluates the law dealing with cybercrimes in Pakistan. It analyses and evaluates the procedure of FIA (Federal Investigation Agency) which is responsible primarily for dealing with cybercrimes in Pakistan.The Population is selected from Pakistan southern area of total users online devices internet and e-commerce . Where electronically cybercrime is commend. Total sapmle size is 297. To collect data asurevy is adapted. The data will be anlysied via softwre Smart Pls. The findings of this study enhance public awareness and contribute to academic. The results are implacable to further study and useful for researchers and publically well being mission. The main addition of this resaech is to analyse the cyber crime activities that are now a days performed by mny hackerds in all over the world. Mostly in Paksitan So, this is a great advancement in research.